Metabarcoding of harmful algal bloom species in sediments from four coastal areas of the southeast China - Wang, Zhaohui; Peng, Liang; Xie, Changliang; Wang, Wenting; Zhang, Yuning; Xiao, Lijuan; Tang, Yali; Yang, Yufeng (Frontiers in Microbiology, 2022)
In the past three decades, harmful algal blooms (HAB) have become more frequent and widespread in southeast Chinese sea areas driven by global change and human activities. Resting stages are regarded as the “seed bank” of algal blooms, and play an important role in initiating HABs. The distribution of resting stages in sediments especially those of HAB species can make good predictions about the potential risk of future blooms, however with limited reports. In this study, surface sediment samples were collected in the four sea areas along the southeast Chinese coasts experiencing different types of human disturbance, including Dafeng Port (DF) in the southern Yellow Sea, Xiangshan Bay (XS), Funing Bay (FN), and Dongshan Bay (DS) in the East China Sea. Diversity and community structure of eukaryotic microalgae in surface sediments were assessed by metabarcoding V4 region of the 18S rDNA, focusing on the distribution of HAB species. Biogenic elements including total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), biogenic silicon (BSi), and moisture content (MC) were analyzed. A total of 454 eukaryotic algal OTUs were detected, which belonged to 31 classes of 9 phyla. Altogether 149 algal species were detected in this study, and 59 taxa have been reported to form resting stages. Eukaryotic algal community was similar in XS, FN and DS of the East China Sea, which were predominated by dinoflagellates. However, algal community was different in DF of the Yellow Sea with massive disturbance of sediments due to the construction of large offshore projects and busy shipping, and characterized by the dominance of chrysophytes and low OTU richness. The distribution of most abundant HAB species showed positive correlations with TN, BSi, and TOC, suggesting that eutrophication and consequent increase in diatom productivity may have a significant influence on the distribution of HAB species and facilitate the occurrence of HABs. Furthermore, HAB species occurred abundantly and widely in FN with dense aquaculture. Our results suggest high potential risks of HABs in the southeast Chinese coast especially in Funing Bay.